2016
DOI: 10.1007/s00005-016-0411-0
|View full text |Cite
|
Sign up to set email alerts
|

Antagonizing Retinoic Acid Receptors Increases Myeloid Cell Production by Cultured Human Hematopoietic Stem Cells

Abstract: Activities of the retinoic acid receptor (RAR)α and RARγ are important to hematopoiesis. Here, we have investigated the effects of receptor selective agonists and antagonists on the primitive human hematopoietic cell lines KG1 and NB-4 and purified normal human hematopoietic stem cells (HSCs). Agonizing RARα (by AGN195183) was effective in driving neutrophil differentiation of NB-4 cells and this agonist synergized with a low amount (10 nM) of 1α,25-dihydroxyvitamin D3 to drive monocyte differentiation of NB-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…On the other hand, RARγ hinders hematopoietic stem cell (HSC) differentiation in favor of their self-renewal and proliferation [ 70 ]. Recent findings suggest that the expression and activities of both RARs coordinate to derive the differentiation lineages of HSCs, and that this is largely dependent on the bioavailability of RA [ 71 ]. Therefore, different doses of RA can determine different cellular lineage specificities.…”
Section: Roles Of Ra On Immunitymentioning
confidence: 99%
“…On the other hand, RARγ hinders hematopoietic stem cell (HSC) differentiation in favor of their self-renewal and proliferation [ 70 ]. Recent findings suggest that the expression and activities of both RARs coordinate to derive the differentiation lineages of HSCs, and that this is largely dependent on the bioavailability of RA [ 71 ]. Therefore, different doses of RA can determine different cellular lineage specificities.…”
Section: Roles Of Ra On Immunitymentioning
confidence: 99%
“…Treatment with retinoids and vitamin D abolishes this effect [ 63 ]. However, when human HSC are cultured with RARα antagonists, the lifespan of the cultures, the number of the progenitors and also the production of monocytes and neutrophils increase, while antagonists of RARγ do not affect the cultures [ 64 ]. This specific role of RARα for human HSC would be different to that above described in mice.…”
Section: Vitamin A/retinoic Acid In Adult Hematopoiesismentioning
confidence: 99%
“…Treatment of hematopoietic stem cells or some leukemia cell lines with the active form of the vitamin D leads to increased monocyte/macrophage differentiation [ 92 , 119 , 120 ], an effect which is not detected in VDR knock-out mice [ 114 , 119 ]. As stated above, when cultured HSC are treated with RA signaling inhibitors, their differentiation is blocked, but retinoids and vitamin D treatment counteract this effect [ 64 ]. Since RARα receptor activation induces granulopoiesis, it has been suggested that VDR and RARα can compete for RXR heterodimerization.…”
Section: Vitamin A/vitamin D Interrelationships In Hematopoiesis Amentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, once binding with LG1506, the RXR-RAR complex recruits silencing mediator of retinoic acid and thyroid hormone receptor (SMRT) corepressors to promoters of target genes such as CD38 , thus inhibiting differentiation of HSCs [46]. Recently, it was found that RARα antagonist increases myeloid cell production and promotes expansion of human HSCs, while RARγ antagonist had no effect due to different sensitivity to ATRA [47]. RXR forms heterodimers with other NRs, including liver X receptor (LXR), thyroid hormone receptor (THR), vitamin D receptor (VDR), peroxisome proliferator-activated receptors (PPARs).…”
Section: Retinoid Acid Signaling and Human Hsc Expansionmentioning
confidence: 99%